India on foot: Internal migrants during COVID-19 in India - Godara, Leelashree; Kumar, Sourav (HAPSc Policy Briefs Series, 2020)
India, home to a population of 1.2 billion, is the country fourth worst hit by COVID-19 in terms of the total number of cases. Within this humongous population is the category of internal migrant workers who have been hit to the extent that their survival is at stake. Introducing this catastrophic hit, this policy brief purposefully elaborates on the challenges faced by India in dealing with this pandemic. The number of internal migrants in India is greater than the total population of the United Kingdom, France, and Germany put together. This unmasks the need for deliberation on the issue of social security of these migrant workers and the role of the state in providing it. Despite measures like the ‘Inter-state workmen act, 1979’, ‘Unorganised Sector Workers Social Security Act, 2008’, and findings of multiple committees, the migrant workers have not been able to integrate into their destination regions to a satisfactory level. Through this paper, the loopholes in these provisions have been highlighted and it has been explained how these provisions failed miserably when put to test by a global pandemic. The authors point out that given the diversity in India’s states, a one-size-fits approach is bound to fail and thus they endorse the demand for greater decentralisation in decision making when it comes to managing a health crisis. The authors recommend a tailor-made and feasible data collection and maintenance strategy as the base on which new provisions for migrant workers could be formulated.